Introduction to design of experiments - Wahid, Zaharah (2018)
A designed experiment is a modern approach in planning an experiment based on sound statistical practices. It offers a number of advantages over the traditional one factor at a time (OFAT) approach to experimentation. It is a structured method of changing multiple factors simultaneously to investigate their effect on one or more response. It detects the interactions among the factors considered for the which cannot be found when changing one factor at a time. It is this interaction that most often prove to be the prime breakthrough improvements. DOE has proven to be extremely useful tool in research and industrial development applications